Quadrupole hyperfine interaction and thermal stability of ZrF 4 .3H 2 O - Rivas, Patricia Claudia (1988)
The quadrupole hyperfine interaction of ZrF4.3H2O is reported. This compound is observed to dehydrate to ZrF4 at 325 K. Spectra taken on cooling were observed to be time dependent, and the rehydration process involved was investigated at 293, 298 and 302 K. Contrary to what had previously been determined in HfF4.3H2O, no intermediate compound was observed to participate in the reaction investigated, thus confirming structural differences already reported to exist between these isoformulae compounds.